ACTN3 R577X and other polymorphisms are not associated with elite endurance athlete status in the Genathlete study - Döring, F. E.; Onur, S.; Geisen, U.; Boulay, M. R.; Pérusse, L.; Rankinen, T.; Rauramaa, R.; Wolfarth, B.; Bouchard, C. (Journal of Sports Sciences, 2010)
Homozygosity for a premature stop codon at amino acid position 577 in the alpha-actinin-3 (ACTN3) gene leads to -actinin-3 deficiency. This genotype is observed in approximately 18% of Caucasians. The ACTN3 R577X polymorphism has been previously associated with indicators of physical performance in several, but not all, studies. We examined the prevalence of R577X (rs1815739) and two additional haplotype tagging single nucleotide polymorphisms (htSNPs) of the ACTN3 gene (rs1791690 and rs2275998) in the Genathlete study comprising 316 male elite endurance athletes ([Vdot]O2max 79.0 ± 3.5 ml/kg·min; mean ± s) from North America, Finland, and Germany and 304 sedentary controls ([V']O2max 40.1 ± 7.0 ml/kg·min) matched by country of origin. The distribution of genotype and allele frequencies between the two groups was tested by Pearson chi-square and/or Fischer exact test. The prevalence of the 577X homozygote genotype was similar in endurance athletes and controls (20% and 17.5%, respectively). The resulting odds ratio for endurance performance in 577X homozygotes compared with 577R-allele carriers was 1.24 (95%CI 0.82-1.87, P = 0.3). The genotype distribution of the two htSNPs and haplotype frequencies did not differ significantly between athletes and controls. In conclusion, our findings indicate that ACTN3 R577X and other SNPs in ACTN3 are not genetic determinants of endurance performance in Caucasian males.